(3CNHGQ GdYdeGA HCNHGQ GdMceGAs - (3Ydj Hf jhSa Hf EHQGgje GdTjHGfj GdbaWj, CHh GdMSf, LeGd GdOjf,J (B646 (3g` s
(3ChdgG (B:s
(3hHYOaEf JhGQjN GdMceGA GdlCOejf hGdadGSaI GdeJCgdjf eeG jLH Ydi GdeSJHUQ JMUjdI s
(3BNQgG (B:s
(3hdg ef ZQGFH GdcJH TQM fgL GdHdGZI Gdedd hGdfMd , efJNH cJGH HWQFjG, ai JQLeI GdaNQi GdQGRi s
(3hgh oeNJUQ GdRhRfis
(3YdjgG hbajI SfI (B1067(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B263s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B20 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs